Revision of the Afrotropical genus Scolopsomorpha Melichar (Hemiptera: Fulgoromorpha: Tropiduchidae) - Constant, Jerome (Zootaxa, 2009)
The genus Scolopsomorpha Melichar, 1912 is moved from the Dictyopharidae to the Tropiduchidae and 2 new species are added to the genus: S. debakkeri (Congo) and S. boulardi (Central African Republic). The genus is provisionally placed in the subtribe Eutropistina Fennah, 1982 of the Eutropistini Kirkaldy, 1906. A lectotype is designated for Scolopsomorpha africana Melichar, 1912. Habitus, male and female genitalia are illustrated and a distribution map is provided.